2018
DOI: 10.1215/00294527-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

On Superstable Expansions of Free Abelian Groups

Abstract: We prove that (Z, +, 0) has no proper superstable expansions of finite Lascar rank. Nevertheless, this structure equipped with a predicate defining powers of a given natural number is superstable of Lascar rank ω. Additionally, our methods yield other superstable expansions such as (Z, +, 0) equipped with the set of factorial elements.2010 Mathematics Subject Classification. 03C45.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 10 publications
(10 reference statements)
0
66
0
Order By: Relevance
“…Then N d s is mutually algebraic for any d ≥ 1 (in fact, it follows from [21] that any structure containing only unary injective functions is mutually algebraic). In each example of a stable expansion of the form (Z, +, A) considered in the sources above, it is shown that A (Z,+) is interpretable in an expansion of N d s by unary predicates, for some d ≥ 1 (in fact, d = 1 suffices for all examples considered in [10], [20], and [26]).…”
Section: Weakly Minimal Abelian Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then N d s is mutually algebraic for any d ≥ 1 (in fact, it follows from [21] that any structure containing only unary injective functions is mutually algebraic). In each example of a stable expansion of the form (Z, +, A) considered in the sources above, it is shown that A (Z,+) is interpretable in an expansion of N d s by unary predicates, for some d ≥ 1 (in fact, d = 1 suffices for all examples considered in [10], [20], and [26]).…”
Section: Weakly Minimal Abelian Groupsmentioning
confidence: 99%
“…Multiplication of ordinals (denoted ·) extends to Ord ∪ {∞} in the obvious way. The following result is [10, Theorem 2.11], and is proved using Proposition 2.4 and techniques similar to the work of Palacín and Sklinos [26] on the expansion of (Z, +) by {2 n : n ∈ N}. Theorem 2.7 (Conant).…”
Section: Bounded Sets In Weakly Minimal Theoriesmentioning
confidence: 99%
See 3 more Smart Citations